The effect of physical fatigue on oscillatory dynamics of the sensorimotor cortex - Fry, Adam; Mullinger, Karen J.; O'Neill, George C.; Brookes, Matthew J.; Folland, Jonathan P. (Wiley, 2018)
Aim: While physical fatigue is known to arise in part from supraspinal mechanisms within the brain exactly how brain activity is modulated during fatigue is not well understood. Therefore, this study examined how typical neural oscillatory responses to voluntary muscle contractions were affected by fatigue. Methods: Eleven healthy adults (age 27±4 years) completed two experimental sessions in a randomised crossover design. Both sessions first assessed baseline maximal voluntary isometric wrist-flexion force (MVFb). Participants then performed an identical series of fourteen test contractions (2 × 100%MVFb, 10 × 40%MVFb, 2 × 100%MVFb) both before and after one of two interventions: forty 12-s contractions at 55%MVFb (fatigue intervention) or 5%MVFb (control intervention). Magnetoencephalography (MEG) was used to characterise both the movement-related mu and beta decrease (MRMD and MRBD) and the post-movement beta rebound (PMBR) within the contralateral sensorimotor cortex during the 40%MVFb test contractions, while the 100%MVFb test contractions were used to monitor physical fatigue. Results: The fatigue intervention induced a substantial physical fatigue that endured throughout the post-intervention measurements (28.9-29.5% decrease in MVF, P<0.001). Fatigue had a significant effect on both PMBR (ANOVA, session × time-point interaction: P=0.018) and MRBD (P=0.021): the magnitude of PMBR increased following the fatigue but not the control interventions, whereas MRBD was decreased post-control but not post-fatigue. Mu oscillations were unchanged throughout both sessions. Conclusion: Physical fatigue resulted in an increased PMBR, and offset attenuations in MRBD associated with task habituation.